Greek Philosophizing as Rhapsodic Telling Deformed by Reflection - Jankauskas, Skirmantas (Problemos, 2009)
Greek philosophizing emerged as a new kind of talking whose specificity was determined by a new theoretical standpoint. Nowadays, we are used to theoretical standpoints, and the standpoint per se seems to be sufficient to view the world anew. However, the world is given to a human as an interrelation of his activity and talking (thinking). The Greek world cosmos was established informally and axiologically by rhapsodic telling. Greek philosophizing was provoked by the imperative “Know thyself” which entrenched Greek philosophers in a new neutral territory of reflection, i.e. theory. Early philosophizing could acquire its contents and aspirations from the rhapsodic telling which established the Greek world. That is why Greek philosophizing inevitably started as an imitation of rhapsodic telling. However, the logical origin of theory gradually took over rhapsodic telling, deformed its content and enfeebled its aspirations. When Greek philosophizing established itself in writing, its ties with the structure of rhapsodic telling were totally broken and the philosophizing isolated itself in theoretical thinking and turned into an anemic activity of writing.